2004
DOI: 10.1080/13803390490509565
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of Clinical Ratings and Neurocognitive Diagnoses in HIV

Abstract: We examined the interrater (IRR) of clinical ratings of neuropsychological (NP) impairment and neurocognitive diagnoses in HIV. Thirty participants with advanced HIV-infection who were enrolled in a multicenter HIV brain banking research project underwent comprehensive NP and neuromedical evaluations. Using a standardized system of guidelines, neuropsychologists from six participating sites independently assigned clinical ratings of NP impairment, as well as multilevel diagnoses reflecting the inferred etiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
316
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 295 publications
(320 citation statements)
references
References 56 publications
(50 reference statements)
3
316
1
Order By: Relevance
“…The t-scores of the individual tests in each domain were averaged to derive NC domain average t scores, and all individual test t-scores were averaged to derive the Global NC Average t score, which reflects global neurocognitive functioning. 18 Consistent with prior literature, Global NC and Domain Average t scores <40…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The t-scores of the individual tests in each domain were averaged to derive NC domain average t scores, and all individual test t-scores were averaged to derive the Global NC Average t score, which reflects global neurocognitive functioning. 18 Consistent with prior literature, Global NC and Domain Average t scores <40…”
Section: Methodssupporting
confidence: 75%
“…were also based on this prior literature. 2,5,18 The Wide Range Achievement Test (WRAT-3) Reading Recognition subtest is a test of single word reading that was administered as a measure of quality of education. 19,20 The psychometric properties of the WRAT-3 Reading subtest are well-established with adequate reliability coefficients (>.90) and validity indices (including convergent and content validity).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were administered a battery of neuropsychological tests that assessed a broad range of cognitive abilities sensitive to HIV impairment (Woods et al, 2004 To investigate prevalence of impairment across domains, we assigned t scores using the following published norms: Heaton et al (1991) for GPDH, GPNDH, TMT-A, and TMT-B; Gladsjo et al (1999) for FAS; Benedict et al (1998) for HVLT; Benedict (1997) for BVMT-R; Tulsky & Price (2003) for the WAIS-III subtests; Diehr et al (2003) for PASAT; and Kongs et al (2000) for the WCST-64. The WAIS-III tests correct for African American, Hispanic, and non-Hispanic White ethnicity (Tulsky & Price, 2003).…”
Section: Neuropsychological Batterymentioning
confidence: 99%
“…The individual tests were also grouped according to the following domains (Woods et al, 2004) as indicated in Appendix I. To investigate prevalence of impairment across domains, we assigned t scores using the aforementioned published norms with the exception of the WAIS-III tests, which used norms from Wechsler (1997).…”
Section: Neuropsychological Batterymentioning
confidence: 99%
“…The individual tests were grouped according to the following domains as previously described (Woods et al, 2004) To investigate prevalence of impairment across domains, we assigned T scores using published norms (Woods et al, 2004). These normatively derived T scores corrected for neuropsychologic testing differences that could be attributable to age, race, and education.…”
Section: Neuropsychologic Assessmentmentioning
confidence: 99%